Transportation and swing reduction for double-pendulum tower cranes using partial enhanced-coupling nonlinear controller with initial saturation. (June 2021) - Tian, Zheng; Yu, Lili; Ouyang, Huimin; Zhang, Guangming
Abstract: Achieving both jib and trolley positioning and swing reduction become more difficult when tower cranes appear double-pendulum characteristic in dynamic. Moreover, in actual applications, the initial output value of actuators is usually physically constrained and the model uncertainties and external disturbances always exist. To solve these problems, a partial enhanced-coupling nonlinear controller with initial saturation is designed and analyzed by Lyapunov technique and LaSalle's invariance theorem. The control performance and strong robustness are severally verified by lots of simulations. Highlights: The load sway suppression problem of double-pendulum tower cranes is investigated. The partial enhanced-coupling nonlinear controller with initial saturation is presented. The control performance is demonstrated by comparative simulations.